Role of GPX4-Mediated Ferroptosis in the Sensitivity of Triple Negative Breast Cancer Cells to Gefitinib - Song, Xiang; Wang, Xinzhao; Liu, Zhaoyun; Yu, Zhiyong (Frontiers in Oncology, 2020)
Gefitinib resistance in triple negative breast cancer (TNBC) is a growing important concern. Glutathione peroxidase 4 (GPX4) is a main regulator of ferroptosis, which is pivotal for TNBC cell growth. We investigated GPX4-mediated ferroptosis in gefitinib sensitivity in TNBC. Gefitinib resistant TNBC cells MDA-MB-231/Gef and HS578T/Gef were constructed and treated with lentivirus sh-GPX4 and ferroptosis inhibitor ferrostatin-1. GPX4 expression, cell viability and apoptosis were detected. Malondialdehyde (MDA), glutathione (GSH), reactive oxygen species (ROS) levels were evaluated. The levels of ferroptosis-related proteins were detected. Subcutaneous tumor model was established in nude mice, and gefitinib was intraperitoneally injected to evaluate tumor growth, apoptosis and Ki-67 expression. GPX4 was increased in gefitinib-resistant cells. After silencing GPX4, the inhibition rate of cell viability was increased, the limitation of colony formation ability was reduced, apoptosis rate was increased, and the sensitivity of cells to gefitinib was improved. After silencing GPX4, MDA and ROS production were increased, while GSH was decreased. Silencing GPX4 promoted ferroptosis. Inhibition of GPX4 promoted gefitinib sensitivity by promoting cell ferroptosis. In vivo experiments also revealed that inhibition of GPX4 enhanced the anticancer effect of gefitinib through promoting ferroptosis. Overall, inhibition of GPX4 stimulated ferroptosis and enhanced TNBC cell sensitivity to gefitinib.